Russia-United States:The Berings Sea - Heininen, Lassi Kalevi; Sergunin, Alexander; Yarovoy, Gleb (ABC-CLIO, 2015)
The U.S.-Russian dispute in the Bering Sea has been an ongoing positional dispute over the maritime boundary between the two countries. The Bering Sea is strategically important to both countries, as well as it is geopolitically important as a route between North America and Eurasia.